Comparison of MRI radiomics-based machine learning survival models in predicting prognosis of glioblastoma multiforme - Zhang, Di; Luan, Jixin; Liu, Bing; Yang, Aocai; Lv, Kuan; Hu, Pianpian; Han, Xiaowei; Yu, Hongwei; Shmuel, Amir; Ma, Guolin; Zhang, Chuanchen (Frontiers in Medicine, 2023)
Objective: To compare the performance of radiomics-based machine learning survival models in predicting the prognosis of glioblastoma multiforme (GBM) patients. Methods: 131 GBM patients were included in our study. The traditional Cox proportional-hazards (CoxPH) model and four machine learning models (SurvivalTree, Random survival forest (RSF), DeepSurv, DeepHit) were constructed, and the performance of the five models was evaluated using the C-index. Results: After the screening, 1792 radiomics features were obtained. Seven radiomics features with the strongest relationship with prognosis were obtained following the application of the least absolute shrinkage and selection operator (LASSO) regression. The CoxPH model demonstrated that age (HR = 1.576, P = 0.037), Karnofsky performance status (KPS) score (HR = 1.890, P = 0.006), radiomics risk score (HR = 3.497, P = 0.001), and radiomics risk level (HR = 1.572, P = 0.043) were associated with poorer prognosis. The DeepSurv model performed the best among the five models, obtaining C-index of 0.882 and 0.732 for the training and test set, respectively. The performances of the other four models were lower: CoxPH (0.663 training set / 0.635 test set), SurvivalTree (0.702/0.655), RSF (0.735/0.667), DeepHit (0.608/0.560). Conclusion: This study confirmed the superior performance of deep learning algorithms based on radiomics relative to the traditional method in predicting the overall survival of GBM patients; specifically, the DeepSurv model showed the best predictive ability.